Let her speak too : Shakespeare's shrews and the modern stage - Kamaralli, Anna (Trinity College (Dublin, Ireland). Department of Drama, 2008)
This thesis takes as its starting point those of Shakespeare's female characters who are upbraided by other characters for speaking inappropriately, or too much, who are, in effect 'shrew' figures. The plays concerned span the full period of Shakespeare's writing career, including the Hemy VI plays. The Taming of the Shrew, Much Ado About Nothing, Measure for Measure, Pericles, and The Winter's Tale, all of which involve female characters who continue to speak and protest in spite of directives to be silent or compliant. In modem Western (particularly Anglophone) society Shakespeare's work is one of the most consistently validated starting points from which we generate cultural meaning for ourselves. I have therefore looked at examples of recent productions (from within the last ten years) of the selected plays, and examined their treatment of these vocal female roles, to see what strategies are currently in operation in the theatre for representing woman as talker. I have also considered the dialogue that surrounds these representations, including how these characters have been reflected on by both theatre practitioners and critics.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin